Study of mixing purple sweet potato and turmeric extract as green corrosion inhibitor for API-5L in NaCl 3.5% environment - Wijaya, Arie; Soedarsono, Johny Wahyuadi; Laksana, Aldi Putra (Jurnal Pendidikan Teknologi Kejuruan, 2021)
Green inhibitors have become a major option for corrosion prevention since people are more aware of environmental damage. It is true that chemical inhibitors are more powerful at preventing corrosion, but its side effects are very harmful to the environment. Purple sweet potato (Ipomoea batatas L) in single use has been proven as an active inhibitor for certain applications. To improve this property, purple sweet potato is used as a mixed with other plants that contain antioxidant agents, such as ginger, melinjo, turmeric, jeera, etc. This paper discussed the effect of applying mixed extract of purple sweet potato with turmeric (Curcuma longa) as a green inhibitor to corrosion rate of API 5L steel in a 3.5% NaCl environment. Turmeric extract contains curcumin and kaempferol antioxidants while purple sweet potato extract contains antocyanin antioxidants. Corrosion rates were analyzed based on weight loss and polarization methods. The results showed the highest inhibitor efficiency was 82.54% achieved by 16 ml of turmeric mixed with 2 ml of purple sweet potato, and the optimum inhibitor efficiency was 74.2% achieved by 8 ml of turmeric mixed with 6 ml of purple sweet potato.